Terrestrial foraging by cacajao melanocephalus ouakary (primates) in Amazonian Brazil: Is choice of seed patch size and position related to predation risk? - Barnett, Adrian Ashton; Almeida, Thais; Spironello, Wilson Roberto; Silva, Welma Sousa; MacLarnon, Ann M.; Ross, Caroline (Folia Primatologica, 2012)
We analyse the behaviour of Cacajao melanocephalus ouakary feeding at patches of germinating seedlings in dried-out flooded forest. Seedlings of Eschweilera tenuifolia (Lecythidaceae) were the most commonly eaten (88.9%). Some seed patches were revisited over several days, while others were consistently ignored. We tested 3 predictions relating uacari terrestrial foraging behaviour to: (1) arboreal escape route proximity, (2) seed patch size choice and (3) temporal patterns of repeat exploitation. Comparison of fed-at and ignored patches revealed significant preferences for larger patches, and for those close to arboreal refuges but distant from dense ground-based vegetation. Support for these predictions is interpreted as evidence for predation risk-sensitive foraging. © 2012 S. Karger AG, Basel.
Keywords: Animals; Appetite; Feeding Behavior; Food Chain; Germination; Lecythidaceae; Nonparametric Test; Observation; Physiology; Pitheciidae; Seed Plant; Time; Animal; Appetitive Behavior; Feeding Behavior; Food Chain; Germination; Lecythidaceae; Observation; Pitheciidae; Seeds; Statistics, Nonparametric; Time Factors; Cacajao Melanocephalus; Eschweilera; Eschweilera Tenuifolia; Lecythidaceae; Primates